Marketing agility in underdog entrepreneurship : A qualitative assessment in post-conflict Sub-Saharan African context - Arslan, Ahmad; Kamara, Samppa; Tian, Anna Yumiao; Rodgers, Peter; Kontkanen, Minnie (Elsevier, 2024)
Extant entrepreneurship literature lacks specific research on how underdog entrepreneurs survive and strive in post-conflict environments. This study seeks to explore the role of marketing agility as an essential capability to survive and exploit business opportunities in post-conflict Sub-Saharan Africa, where institutional voids and volatility coexist. The empirical research design comprises of multiple case studies of sixteen underdog (war-affected) entrepreneurs in Liberia and Sierra Leon; both countries which went through civil war and violent internal strife in recent past. The study findings reveal that marketing agility and its dimensions, i.e., robustness, responsiveness, and proactiveness, are critical for underdog entrepreneur’s business’s survival. Finally, the findings also show that institutional context, volatility, and individual experiences of entrepreneurs tend to influence the manifestation of this marketing agility.
Keywords: Conflict; Marketing agility; Sub-Saharan Africa; Underdog entrepreneurship; fi=Markkinointi|en=Marketing|